2018
DOI: 10.3390/ijms19071833
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Binding Proteins S100A8 and S100A9: Investigation of Their Immune Regulatory Effect in Myeloid Cells

Abstract: High expression levels of the calcium-binding proteins S100A8 and S100A9 in myeloid cells in kidney transplant rejections are associated with a favorable outcome. Here we investigated the myeloid cell subset expressing these molecules, and their function in inflammatory reactions. Different monocyte subsets were sorted from buffy coats of healthy donors and investigated for S100A8 and S100A9 expression. To characterize S100A9high and S100A9low subsets within the CD14+ classical monocyte subset, intracellular S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 43 publications
1
39
0
1
Order By: Relevance
“…Multiple studies successfully detected mRNA expression with the SmartFlare technique (McClellan et al 2015;Kronig et al 2015;Lahm et al 2015;Seftor et al 2014;Li et al 2016). However, two recent studies showed that different SmartFlare probes were not able to specifically detect their target mRNAs in cell lines and monocytes (Czarnek and Bereta 2017;Yang et al 2018). Here we showed that SmartFlare is an effective tool to detect TWIST1 gene expression in living BMSCs, but differences in probe concentration, incubation time and cellular uptake can influence the SmartFlare sensitivity and possibly lead to misinterpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies successfully detected mRNA expression with the SmartFlare technique (McClellan et al 2015;Kronig et al 2015;Lahm et al 2015;Seftor et al 2014;Li et al 2016). However, two recent studies showed that different SmartFlare probes were not able to specifically detect their target mRNAs in cell lines and monocytes (Czarnek and Bereta 2017;Yang et al 2018). Here we showed that SmartFlare is an effective tool to detect TWIST1 gene expression in living BMSCs, but differences in probe concentration, incubation time and cellular uptake can influence the SmartFlare sensitivity and possibly lead to misinterpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally it was applied to investigate a Nodal expressing subpopulation of melanoma cells (Seftor et al 2014), and to study a subpopulation of human BMSCs with an enhanced osteogenic potential (Li et al 2016). However, other studies did not find a correlation between the SmartFlare fluorescence intensity and mRNA expression measured by RT-PCR (Czarnek and Bereta 2017;Yang et al 2018). In addition, Czarnek et al (2017) found that the SmartFlare signal intensity correlates with the probe uptake ability of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, S100A8 induction by Escherichia coli DNA required IL10 signalling, while S100A8 participated in stimulation of IL10 secretion by human monocytes . Overexpression of S100A8 and S00A9 in macrophages led to enhanced IL10 gene expression . S100A8 and S100A9 proteins have both pro‐inflammatory (chemotactic) and anti‐inflammatory properties (suppress migration, repulsion of neutrophils) .…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised clustering segregated 3 populations of granulocytes/neutrophils that were marked by unique gene expression ( Figure 3A). Relative gene-expression compared to all other cell populations as log2 fold-change was plotted in a heat map ( Figure 3B) and violin plot ( Figure 3C Figure 3B-C, and S1 Table) (23)(24)(25)(26)(27)(28)(29). Based on the gene expression profiles, cluster 8 was identified as "inflammatory neutrophils" and cluster 3 was identified as "gMDSC/autoreactive neutrophils".…”
Section: Three Distinct Neutrophil Populations Revealed By Scrna-seqmentioning
confidence: 99%